Pengalaman Informasi Followers Akun Instagram @Viviatal dalam Memenuhi Kebutuhan Informasi Mengenai Self Development - Ilham, Muhammad; Primadesi, Yona (YASIN, 2024)
The phenomenon of needing information regarding self-development is considered important. To meet these needs, the Instagram account @viviatal is an alternative. After the information needs are met, of course followers of the @viviatal account will get an information experience. This research aims to determine the information experience felt by followers of the Instagram account @viviatal. This research uses a qualitative method with a phenomenological approach. The information in this research was determined using a purposive sampling technique. Collection techniques were carried out by means of observation, interviews and documentation. The analysis technique used is thematic analysis technique, namely identifying patterns and forming new themes based on the data collected. The results of this research show that the Instagram account @viviatal (1) is the result of identifying sources of information, (2) becomes a media that plays a role, and (3) has an impact in increasing insight, consideration in decision making, and has a positive impact on followers of the Instagram account @viviatal.